Hubungan Power Otot Lengan, Power Otot Tungkai dan Fleksibilitas Pergelangan Tangan dengan Hasil Jumping Smash dalam Permainan Bulutangkis. - Kamaludin, Ikmal; Raharja, Didik Subhakti Prawira; Rusdiyanto, Rajip Mustafillah (Jurnal Kepelatihan Olahraga, 2023)
To be able to get points effectively, one of them can be obtained by doing a jump smash, but to be able to do well it needs to be supported by several components of physical conditions. This study wants to know the relationship between the components of physical conditions that support success in doing jumping smashes. Correlational research was conducted at PB. Buana Majalengka with a sample of 7 advanced athletes, and the instrument used uses a test to measure arm muscle power, leg muscle power, wrist flexibility and jumping smash results. The results show that together, the physical condition components provide a very strong support for the results of the jumping smash. Apart from that, it is necessary to pay attention to other components such as the timing of taking the ball and determining the position before hitting.